2010
DOI: 10.1007/s10404-010-0739-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanomanipulation of single influenza virus using dielectrophoretic concentration and optical tweezers for single virus infection to a specific cell on a microfluidic chip

Abstract: A major problem when analyzing bionanoparticles such as influenza viruses (approximately 100 nm in size) is the low sample concentrations. We developed a method for manipulating a single virus that employs optical tweezers in conjunction with dielectrophoretic (DEP) concentration of viruses on a microfluidic chip. A polydimethylsiloxane microfluidic chip can be used to stably manipulate a virus. The chip has separate sample and analysis chambers to enable quantitative analysis of the virus functions before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 18 publications
(17 reference statements)
0
42
0
Order By: Relevance
“…PCC 6803 as single cell measurement This method can be used to measure the physiological properties in a single cell and can be used for analysis of cell to cell communication. For example, analysis of influenza virus activity inside the infected cell will be realized by measuring the physiological conditions before and after virus infection [21]. This technique will make a great contribution in cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…PCC 6803 as single cell measurement This method can be used to measure the physiological properties in a single cell and can be used for analysis of cell to cell communication. For example, analysis of influenza virus activity inside the infected cell will be realized by measuring the physiological conditions before and after virus infection [21]. This technique will make a great contribution in cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…For example, analysis of influenza virus activity inside the infected cell will be realized by measuring the physiological conditions before and after virus infection [26]. This technique will make a great contribution in cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that it is possible to trap and accumulate an ensemble of virus particles from a static solution using microDEP [10][11][12], but capture and manipulation of individual virus particles, particularly those from a highflow-rate solution (as needed for the rapid concentration of dilute virus samples) have not been developed. A few studies have demonstrated that single virus particles in a flow can be trapped between the gap of two nanoelectrodes [13] or using optical tweezers coupled with a microDEP concentrator [14]. However, these techniques are expensive and can only be used in low-throughput studies.…”
Section: Introductionmentioning
confidence: 99%